Assessing landscape design of small towns in Russia. Issue 3 (17th August 2021) - Karandeev, Alexander; Sedykh, Olga; Yartseva, Elizabeth
Abstract : The article deals with issues related to the urban design assessment of a small towns in the Lipetsk Region. The creation of a comfortable living environment is one of the most important functions of urban landscapes' ecosystem. This paper explains a methodology of assessing the urban public spaces using three-dimensional mapping, data collected through remote sensing and field research as well as questionnaire that included a comprehensive score. The score description contains an auxiliary category that helps assigning the grade of the score. A methodology for describing towns' landscapes, developed on the basis of a questionnaire is applied. The authors adhere to the requirement of landscape factors equivalence as one of the provisions that determine landscape design. Research studies have shown that according to the total assessment score, the level and quality of urban landscape design are highly appreciated by residents. Parks and public green areas are a key link in the sustainable development of urban areas and they are not included in the general territory of small towns and are located on small land plots. Why is this the case? The landscape design of small towns in Russia is poorly studied and its scientific assessment requires further development.